Cutaneous Vasculopathy in a COVID-19 Critically Ill Patient: A Histologic, Immunohistochemical, and Electron Microscopy Study. (7th April 2021) - Kyriakoudi, Anna; Pontikis, Konstantinos; Tsaraklis, Athanasios; Soura, Efthymia; Vourlakou, Christine; Kossyvakis, Athanasios; Potamianou, Efstathia; Kaniaris, Evangelos; Ioannidou, Iliana; Mentis, Andreas; Kloukina, Ismini; Daganou, Maria; et al.
Abstract : We describe a critically ill, SARS-CoV-2 positive patient with respiratory failure and thrombotic/livedoid skin lesions, appearing during the course of the disease. The biopsy of the lesions revealed an occlusive, pauci-inflammatory vasculopathy of the cutaneous small vessels characterized by complement and fibrinogen deposition on vascular walls, pointing to a thrombotic vasculopathy. Transmission electron microscopy of the affected skin failed to reveal any viral inclusions. Clinical evaluation and laboratory findings ruled out systemic coagulopathies and disseminated intravascular coagulation, drug-induced skin reaction, and common viral rashes. Our hypothesis is that the, herein evidenced, microvascular occlusive injury might constitute a significant pathologic mechanism in COVID-19, being a common denominator between cutaneous and pulmonary manifestations.